Pengaruh Kualitas Pelayanan, Promosi Dan Lokasi Terhadap Kepuasan Konsumen Pada PT. Sun Kado Medan - Novryanti Pagan; Eka Purnama Sari (Pusat Riset dan Inovasi Nasional, 2023)
The purchase decision is the root of the achievement of a sale which on the purchase decision has an impact on turnover and sustainability of each organization. The purchase decision is one of the form of consumer behavior in using a product. In using a product to make a buying decision, consumers will go through a process that is a description of consumer behavior analyze various options to make decisions in make a purchase. The purchase target will be achieved if the attributes Purchasing drivers are met by the company, one of these attributes is: Quality of service, promotion, location.The method used in this research is a quantitative method with the number of samples set as many as 97 respondents. The analysis used includes the test validity, reliability test, classical assumption test, and multiple linear analysis test and coefficient of determination. The results of this study indicate that partially. Service quality affects satisfaction, however for the promotion variable has no positive and significant effect partially to customer satisfaction. And location has a positive and significant effect on customer satisfaction. For the simultaneous test, the quality of service, promotion and location has an effect on customer satisfaction.